Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Konsumen Bengkel Toyota di Auto2000 Cabang Marelan - Irvan Affandi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to determine the influence of service quality and facilities on customer satisfaction of Toyota workshops at Auto2000 Marelan Branch. This research is motivated by a decrease in customer satisfaction based on internal survey data in 2025. The research method used is quantitative research with an associative approach. The population in this study is consumers who have used service services at the Toyota Auto2000 Marelan workshop, with sampling using purposive sampling techniques. Data collection was carried out through the distribution of questionnaires to respondents. The data analysis techniques used include validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, F test, and determination coefficient using the help of SPSS. The results of the study show that the quality of service has a positive and significant effect on consumer satisfaction. Facilities also have a positive and significant effect on consumer satisfaction. Simultaneously, the quality of service and facilities has a significant effect on the satisfaction of Toyota workshop customers at Auto2000 Marelan Branch. Thus, improving the quality of services and facilities needs to be carried out on an ongoing basis to increase consumer satisfaction.